Accuracy of vertical bitewing and bisect periapical radiography techniques in anterior mandibular teeth interdental bone resorption - Mohamad Shah Abouei; Ehsan Hekmatian E; Mahdi Adibrad; Ayoob Bahador Ghobadi (Isfahan University of Medical Sciences, 2009)
Introduction: Alveolar bone level is changed due to the balance between bone formation and resorption. Radiographic examination has an important role in the diagnosis and treatment of periodontal diseases. This study was performed to compare the accuracy of vertical bitewing and periapical radiography in anterior mandibular teeth interdental bone resorption using grid sheet.Materials and Methods: A total of 20 patients who all needed periodontal surgery on their anterior mandibular region were included. Before surgery, using grid sheet, 3 periapical radiographs and 3 vertical bitewing radiographs were taken from the anterior mandibular region, and the distance between CEJ and the crest of alveolar bone were measured on the scaled radiographs. During periodontal surgery the real amount of bone resorption was measured via Williams probe. The collected data were then analyzed by paired-t-test.Results: The mean of alveolar bone resorption on vertical bitewing radiography was 3.88 ± 1.06 and 3.97 ± 0.97 for mandibular incisors and mandibular canines respectively. On periapical radiography however, the same value was 3.80 ± 0.75 for mandibular incisors, and 3.90 ± 1.11 for mandibular canines. Applying Williams probe during surgery, the mean value of real alveolar bone resorption was found to be 3.20 ± 1.20 for mandibular incisors, and 3.18 ± 1.03 for mandibular canines.Conclusion: Based on the findings, there were significant differences between the findings on periapical and vertical bitewing radiographs with the real amount of bone resorption recorded during surgery. However, the difference between the accuracy of bite wing and periapical radiography in measuring the amount of alveolar bone resorption in anterior mandibular region was not significant.